(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to the search for effective combinations of methods of teaching medical disciplines for students of the specialty "Physical Culture and Sports", which allow providing basic knowledge about the conditions of a healthy existence of an athlete and functional changes in the body during physical exertion. Knowledge of sports physiology and the basics of hygiene and ecology provides fundamental professional training for future coaches. To improve the effectiveness of teaching in classroom, blended or distance learning environments, the study used both traditional teaching methods (narration, demonstration, lecture) and innovative ones (interactive presentations, peer-to-peer method, microphone method, heart attack method, use of e-learning systems). The information block and algorithms for performing practical work in the discipline "Hygiene with the basics of ecology" were presented in methodological recommendations posted in the e-learning system, as well as presentations, video materials and test tasks. The practical work was recorded in the protocols of their implementation, drawn up in the form of a workbook. In the teaching of "Sports Physiology", priority was given to the development of practical skills in assessing physical development and physical condition, conducting functional tests and their interpretation, testing the level of fatigue, compiling and correcting the athletes’ diet. Therefore, the assessment was carried out mainly by demonstrating skills in an classroom or video format. The analysis of the effectiveness of training was carried out based on the results of the survey analysis and student success indicators. The authors concluded that the combination of the proposed methods and means of learning allows applicants for the specialty "Physical Culture and Sports" to better master the curricula in the disciplines "Hygiene with Fundamentals of Ecology" and "Sports Physiology" in classroom, blended or distance learning. The implementation of blended learning in the educational process of higher education institutions expands the opportunities for applicants to achieve practical learning outcomes in accordance with educational standards and professional training challenges.